The influence between migraine preven drugs and sumatriptan succinate on motor activity - Novak, Edison Matos; Kowacs, Pedro André; Carvalho, Guilherme Armando de; Savio, Mariane Christina; Augusto, Lucas Pires; Borges, Conrado Regis; Gustavo Ribas; Guinski, Giovana Costa; Sandra Monarin; Utiumi, Marco Antonio Takashi; Piovesan, Élcio Juliato (Headache Medicine, 2024)
Background and aim The motor effect of sumatriptan succinate (SS) and whether or not it is associated with different classes of migraine preventive drugs has yet to be studied. We aimed to analyze such drugs' influence on animal motor activity, verifying their effect when used alone or in combination. Methods Male Norvegicus rats (n=98) were treated with routinely prescribed migraine preventive drugs and divided into five groups: isotonic saline solution (ISS, control), propranolol, topiramate, flunarizine, and amitriptyline. After five days of daily treatment, the animals received acute treatment with either ISS or Sumatriptan succinate (SS). The drug's influence on motor function behavior was assessed with the rotarod and open field tests. Results Propranolol and flunarizine interfered with the motor activity (p=0.006 and 0.002, respectively). SS did not cause motor changes when administered alone. However the SS combined with amitriptyline increased the number of rearings (p=0,045) and reduced the immobility time (p=0.041). Conclusions SS exerted no motor effect, although flunarizine and propranolol could produced motor interference.